The Degree of Ethical Leadership Practice Among School Leaders in The Public Schools for Boys in Dammam City - Almahwari, Hadi Ahmed (Journal of Educational and Psychological Sciences, 2022)
The present study aimed to identify the degree of practicing ethical leadership among school leaders in state- owned schools for boys in Dammam. To achieve the objectives of the study, the descriptive survey approach was used, and the questionnaire was used as a tool for data collection, and a random sample of (425) teachers was chosen. The study concluded a number of conclusions, the most important of which are: that the degree of practicing ethical leadership by school leaders was extreme, with an average of (3.98). In light of these conclusions, the study recommended school leaders to continue practicing ethical leadership because of the impact of leader's ethics on raising the level of teachers’ performance, and prompting them to make all the efforts that would contribute to achieving the objectives. The study also recommended the Education Department in Dammam to support and enhance the practice of ethical leadership by providing training programs and workshops on ethical leadership and the results it achieves.
Keywords: degree of practice; leadership; moral leadership; school leadership